Plasticity of muscle synergies through fractionation and merging during development and training of human runners - Vincent C. K. Cheung (Nature Portfolio, 2020)
Motor commands for human locomotion are generated by combination of muscle synergies. In humans, muscle synergies for running exhibit considerable plasticity during child-to-adult development and adult training to meet the constantly changing biomechanical and efficiency demands.